Development of Marketing Strategies PT Ashar Global Mandiri In Increasing Sales of Housing Products Using The QSPM Method (Study on Pesona Alam Housing In Madiun City) - Thoriq Amir Sholehuddin; Elia Ardyan (International Journal Labs, 2025)
This research is based unstable phenomenon of house sales at PT Ashar Global Mandiri unstable. The aim of this research is to formulate the development of a marketing strategy for PT Ashar Global Mandiri in increasing sales of housing products using the QSPM method. The design used in this research is a qualitative method with a phenomenological approach. The research was conducted from August 2023 - January 2024. The number of informants used was three people. The methods used in collecting data consisted of interviews, questionnaires and observations. Meanwhile, to test the validity of the data using triangulation. The triangulation test used is source triangulation. The data in this research will be processed using the NVivo14 program. The results of this research show that based on the SWOT diagram, PT Ashar Global Mandiri is located in Quadrant I, which means a good strategic position. The strategy that PT Ashar Global Mandiri can use is to carry out market development and product development to win a better market. Priorities in developing marketing strategies that can be carried out are improving promotional strategies. Promotional strategies that can be implemented are creating a YouTube channel and collaborating with influencers in reviewing and promoting Pesona Alam housing, holding joint promotional events such as property exhibitions or open houses to introduce housing to potential buyers, and participating in other housing events around the city of Madiun.